Lead isotopes link copper artefacts from northwestern Botswana to the Copperbelt of Katanga Province, Congo. (May 2020) - Stephens, Jay; Killick, David; Wilmsen, Edwin; Denbow, James; Miller, Duncan
Abstract: Copper was highly valued in sub-Saharan Africa for jewellery and as a store of wealth, but was rarely used for tools or weapons. The Central African Copperbelt is one of the world's largest copper deposits, and is known to have been mined since at least 400–600 cal CE, but has seen very little archaeological investigation. We measured lead isotope ratios and trace element concentrations in 20 copper objects, dating between ca. 650 cal CE and ca. 1200 cal CE, from two sites in the Tsodilo Hills in northwestern Botswana. The results show unequivocally that almost all derive from Copperbelt ore deposits in Katanga Province, Democratic Republic of the Congo, at least 1050 km from Tsodilo. Our results are very similar to those recently obtained for a suite of 45 copper ingots, dated between 9th and 18th centuries cal CE, most of which are from cemeteries in the Upemba Depression, about 200 km north of the Copperbelt (Rademakers et al., 2019). Highlights: Radiogenic lead isotopic ratios show that Tsodilo Hills copper came from the Central African Copperbelt >1000 km away. Tsodilo Hills copper is isotopically and chemically similar to ingots from the Upemba Depression cemeteries of southern DRC. The very high purity of much Tsodilo and Upemba copper suggests smelting of pure malachite.